Fading Legacies: Human Capital in the Aftermath of the Partitions of Poland - Andreas Backhaus (European Historical Economics Society (EHES), 2019)
This paper studies the longevity of historical legacies in the context of the formation of human capital. The Partitions of Poland (1772-1918) represent a natural experiment that instilled Poland with three different legacies of education, resulting in sharp differences in human capital among the Polish population. I construct a large, unique dataset that reflects the state of schooling and human capital in the partition territories from 1911 to 1961. Using a spatial regression discontinuity design, I find that primary school enrollment differs by as much as 80 percentage points between the partitions before WWI. However, this legacy disappears within the following two decades of Polish independence, as all former partitions achieve universal enrollment. Differences in educational infrastructure and gender access to schooling simultaneously disappear after WWI. The level of literacy converges likewise across the former partitions, driven by a high intergenerational mobility in education. After WWII, the former partitions are not distinguishable from each other in terms of education anymore.
Keywords: N34; I20; O15; H75; 330; Poland; Human Capital; Education; Persistence